Unveiling an oral hemangiolymphangioma - Ferreira-Santos, Rívea Inês; Santos, Kamilla Alves [UNESP]; Scherma, Alexandre Prado; León, Jorge Esquiche; Kaminagakura, Estela [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
Hemangiolymphangioma is a very rare vascular malformation that develops as a combination of dilated venous and lymphatic vessels. We describe an unusual case of hemangiolymphangioma of the tongue affecting an adult man who complained of an uncomfortable, slowly progressing exophytic irregular dark red-violaceous nodular mass on his tongue that impaired speech and swallowing for two weeks. The clinical differential diagnoses were Kaposi’s sarcoma and a COVID-19-related lesion. A complete blood count and serology for HIV-1 and 2 and RT-PCR for COVID-19 were requested and results were negative. An incisional biopsy was performed. Microscopically, the lesion exhibited several dilated vessels lined by normal-appearing endothelial cells, some filled with prominent intravascular erythrocytes and others containing proteinaceous eosinophilic material resembling lymphatic vessels, in close association with hyperkeratosis, papillomatosis, and acanthosis. From immunohistochemical analysis, most vessels were found to be CD34 positive, some highlighted by α-SMA, whereas D2-40 was focal. Positive staining for some lymphatic and blood vessel markers, i.e., D2-40 and CD34, respectively, indicates a mixed derivation of the lesion. HHV-8 was negative. Clinical features, the congested blood vessels with ectasia in intimate association with hyperplastic epithelium, and the immunohistochemical profile supported the final diagnosis of oral hemangiolymphangioma. The patient underwent minimally invasive surgical excision with no intercurrences. After 18 months of follow-up, there were no signs of relapse.
Keywords: Angiokeratoma; case reports; COVID-19; lymphangioma; tongue